Biodegradation of Organo phosphorous Pesticide Dichlorvos by bacteria isolated from field sample - Pandey, Ravi; Aparna, Y. (International Journal of Scientific Research in Biological Sciences, 2019)
The extensive use of pesticides is considered to be one of the major causes of soil and water pollution in agricultural sector. As it enters the food chain, humans on the other hand are directly or indirectly victimized. In order to counteract the situation, such contaminants need to be removed from the environment. The safest approach to clean the environmental pollution in an eco-friendly way is by employing microorganisms, a process termed as biodegradation. Dichlorvos is an organophosphorus pesticide widely used as insecticide to control pest in agriculture.In the present study an attempt was made to screen for potential Dichlorvos degrading bacteria. The soils collected from various field samples are subjected to enrichment culture technique using various concentrations of pesticides in minimal salt medium. Of all the organisms screened only four isolates labelled as SA, SB, SC and SD showed degradative activity. Organophosphate enzyme assay was performed to confirm the degradation by using UV-Visible spectrophotometer. However further studies are to be done to check whether the cultures are showing complete degradation, partial degradation or bioconversion.